The fluctuations of China's economic growth since the reform and opening up and the rational countermeasures. Issue 2 (2nd December 2019) - Jian, Xinhua; Yu, Jiang
Abstract : Purpose: The purpose of this paper is to review the four large and two small fluctuations in China's economic growth since the reform and opening up, which can be further divided into five periods of economic upturn and six periods of economic downturn. Design/methodology/approach: This paper also analyzes the performance, causes and practical countermeasures of these fluctuations and summarizes the experience and lessons from the eight aspects of dealing with economic downturn and stabilizing growth since the reform and opening up. Findings: At last, the paper puts forward some measures to cope with economic downturn and stabilize growth under the new normal in the new era. Originality/value: Any country's economic growth is a tortuous process with many fluctuations. The rate of economic growth cannot rise or go down straight for a long time, and China's economic growth is no exception. The drastic fluctuations of economic growth can lead to serious overproduction, waste of resources, increased unemployment, decreased income or supply shortages, rising prices and decline of living standards.